The relevance of climate change and sustainability in nursing education: a cross-sectional study of students’ perspectives - Jennie Aronsson; Marie Elf; Paul Warwick; Riccardo LoMartire; Anna Anåker (BMC Nursing)
Abstract Background As climate change continues to challenge global health, nursing education must evolve to prepare future nurses for the impacts on care delivery and promote sustainable practices within the healthcare system which is itself a contributor to the climate crisis through emissions and waste. In this study we aimed to i) explore undergraduate nursing students’ attitudes towards and awareness of climate change and sustainability issues and its inclusion in nursing education at a Swedish university, and ii) explore differences in awareness and attitudes across student groups in different semesters. Methods In this cross-sectional descriptive research study, nursing students from six groups (semester 1,2,3,4,5,6) of a three-year BSc Nursing programme were asked to complete the Sustainability Attitudes in Nursing Survey (SANS_2) questionnaire. Descriptive statistics were used to present mean scores for each item, and the Kruskal-Wallis test was used to identify differences in responses between different student groups. The Strengthening the Reporting of Observational Studies in Epidemiology (STROBE) statement has been used to report this research. Results A total of 211 (32%) students completed the questionnaires. The findings showed that nursing students across the six semesters had relatively good awareness of, and positive attitudes towards, sustainability and climate change (no mean rating below 4 on a scale 1–7). Statistically significant differences between student groups were found in four out of nine items of the SANS_2 questionnaire, with students in their second semester consistently providing the highest ratings (p < 0.05). Notably, the lowest ratings across these four items were provided by students in their last year of the programme. Conclusions This study found that whilst students initially felt equipped to address sustainability issues and climate change in practice, this confidence appears to diminish by the programme’s end, raising concerns about the preparedness of the future workforce. This underscores the urgency and importance of continuous reinforcement of sustainability concepts in nursing education, aligning with a spiral curriculum approach which advocates for reiterating themes throughout the curriculum to deepen understanding. Clinical trial number Not applicable.